Mikulicz’s disease and Küttner’s tumor as manifestations of IgG4-related diseases: a review of the literature - Bartłomiej Kamiński (Termedia Publishing House, 2020)
According to a new concept for the classification and division of autoimmune diseases, Mikulicz’s disease and Küttner’s tumor belong to immunoglobulin G4-related diseases (IgG4-RD) and fulfil their diagnostic criteria. The aim of this study was to summarize the new classification concepts of IgG4-RD in the head and neck area and to review their clinical, histopathological and serologic criteria and the methods used in the diagnostic workup with respect to their advantages, limitations and differentiative value. The PubMed, Web of Science, Google Scholar, and Scopus databases were searched for articles published between 2009 and 2019 using the following key words: IgG4-related diseases, Mikulicz’s disease, Küttner’s tumor, salivary glands, xerostomia. Results of the review of the literature revealed that Mikulicz’s disease and Küttner’s tumor fulfil the same diagnostic criteria but may manifest different clinical symptoms which determine the choice of the different diagnostic tools.